The Effects of Combined Endurance and Strength Training on Endurance and Sprint Performance in Young Elite Football Players - Ceviz, Ebru; Genc, Harun; Sabanci, Gokhan (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2025)
The aim of this study is to investigate the effects of a 12-week combined endurance and resistance training program on endurance and sprint performance in U-17 male football players. A total of 44 players were divided into two groups: the Combined Training Group (CTG, n=22) and the Football Training Group (FTG, n=22). Both groups continued their regular football training throughout the study period. In addition to football training, the athletes in the experimental group performed combined endurance and resistance exercises targeting major muscle groups four times a week to improve overall conditioning and performance. A two-way repeated measures ANOVA test was used to determine the differences between pre-test and post-test measurements. The CTG showed a 23.95% improvement in the Yo-Yo IR1 test distance (p=.000) and a 4.11% improvement in the 25 m sprint time (p=.000). In contrast, no statistically significant changes were observed in either performance variable in the FTG, who only participated in regular football training (p>.05). In conclusion, a well-structured 12-week concurrent endurance and resistance training program can significantly improve both aerobic endurance and sprint performance in U-17 male football players. Moreover, concurrent training offers important advantages, especially during developmental stages such as U-17, by saving training time, maximizing performance gains, and allowing greater focus on sport-specific skill development.